The Vallecas Project: A Cohort to Identify Early Markers and Mechanisms of Alzheimer’s Disease - Olazarán, Javier; Valentí, Meritxell; Frades, Belén; Zea-Sevilla, María Ascensión; Ávila-Villanueva, Marina; Fernández-Blázquez, Miguel Ángel; Calero, Miguel; Dobato, José Luis; Hernández-Tamames, Juan Antonio; León-Salas, Beatriz; Agüera-Ortiz, Luis; López-Álvarez, Jorge; et al. (Frontiers in Aging Neuroscience, 2015)
Introduction. Alzheimer’s disease (AD) is a major threat for the well-being of an increasingly aged world population. The physiopathological mechanisms of late-onset AD are multiple, possibly heterogeneous, and not well understood. Different combinations of variables from several domains (i.e., clinical, neuropsychological, structural, and biochemical markers) may predict dementia conversion, according to distinct physiopathological pathways, in different groups of subjects. Methods. We launched the Vallecas Project (VP), a cohort study of non-demented people aged 70 to 85, to characterize the social, clinical, neuropsychological, structural, and biochemical underpinnings of AD inception. Given the exploratory nature of the VP, multidimensional and machine learning techniques will be applied, in addition to the traditional multivariate statistical methods. Results. A total of 1,169 subjects were recruited between October 2011 and December 2013. Mean age was 74.4 years (SD 3.9), 63.5% of the subjects were women, and 17.9% of the subjects were carriers of at least one ε4 allele of the apolipoprotein E (APOE) gene. Cognitive diagnoses at inclusion were as follows: normal cognition 93.0% and mild cognitive impairment (MCI) 7.0% (3.1% amnestic MCI, 0.1% non-amnestic MCI, 3.8% mixed MCI). Blood samples were obtained and stored for future determinations in 99.9% of the subjects and 3T magnetic resonance imaging (MRI) study was conducted in 89.9% of the volunteers. The cohort is being followed up annually for four years after the baseline. Conclusion. We have established a valuable homogeneous single-center cohort which, by identifying groups of variables associated with high risk of MCI or dementia conversion, should help to clarify the early physiopathological mechanisms of AD and should provide avenues for prompt diagnosis and AD prevention.